PELAKSANAAN ALOKASI DANA DESA (ADD) DALAM BIDANG PEMBERDAYAAN MASYARAKAT DI KABUPATEN KONAWE - Jopang Jopang; Arifin Utha; Eko Harianto (Journal Publicuho, 2018)
ABSTRACTThe shift in the principle of setting of the principle of "decentralization" and "residuals" on previous legislation became the principle of subsidiarity and the principle of recognizing in Act No. 6 of the year 2014 of the village became hope and renewed energy for the village to be able to determine the position, role and authority over him. This research aims to analyze the implementation of the budget of the village Fund in the field of community empowerment in Wowonii Island.This research uses qualitative descriptive approach. The subject specified in purposive that describe the representation of topology village (the region of mainland coast, and inland). The technique of data collection was done through interviews, the study document, Focus Group Discussions and observations. The technique of data analysis performed with the interactive approach in the form of model reduction data, display data, verification and conclusion.The results of showing the budget of the village during the time brackets 4 (four) years have contributed to the village and community in the County Wowonii Island. Although the budget of the fund of the village in the field of development and the empowerment of the community very small but their impact is very beneficial for community interests. The Village Government and the Improved Quality in 2014 The Village Government and the Improved Quality in 2014, the Village Fund Budget Year 2014, 2015 and 2016, do not contribute directly to the community. of community service. The village Fund Budget activity 2015-2017 year, especially through the village of interior Shield, is considered to be highly contributing to society, especially the poor and women. Surgical program home and Businesses Productive is the flagship program of the community throughout the village District Wowonii Island.    Keywords: Implementation, Allocation Of The Village Fund, Community Empowerment